Prioritizing test cases for resource constraint environments using historical test case performance data - Fazlalizadeh, Y.; Khalilian, A.; Azgomi, M.A.; Parsa, S. (2009 2nd IEEE International Conference on Computer Science and Information Technology, 2009)
Regression testing has been widely used to assure the acquirement of appropriate quality through several versions of a software program. Regression testing, however, is too expensive in that, it requires many test case executions and a large number of test cases. To provide the missing flexibility, researchers introduced prioritization techniques. The aim in this paper has been to prioritize test cases during software regression test. To achieve this, a new equation is presented. The proposed equation considers historical effectiveness of the test cases in fault detection, each test case's execution history in regression test and finally the last priority assigned to the test case. The results of applying the proposed equation to compute the priority of regression test cases for two benchmarks, known as Siemens suite and Space program, demonstrate the relatively faster fault detection in resource and time constrained environments.